2023
DOI: 10.1021/acsami.2c22904
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Studies of Working Mechanisms for Self-Driven Narrowband Perovskite Photodetectors

Abstract: Self-driven narrowband perovskite photodetectors have recently attracted significant attention due to their simple preparation, high performance, and amenability for system integration. However, the origin of narrowband photoresponse and the related regulation mechanisms still remains elusive. To address these issues, we herein perform a systematic investigation by formulating an analytic model in conjunction with finite element simulation. The optical and electrical simulations have resulted in design princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Lead halide perovskite nanocrystals (PNCs) possess remarkable optical properties, such as high photoluminescence quantum yield (PLQY), large absorption coefficient, wide range bandgap tunability, and narrow emission line width. These characteristics make PNCs a promising material for optoelectronic applications, such as light-emitting diodes (LEDs), solar cells, , and photodetectors. , However, the ionic nature renders PNCs susceptible to light, heat, water, and polar solvents. Recent studies have shown that the rapid degradation of PNCs is primarily caused by the instability of their surface capping. The bonding between surface halides and ammonium ligands, facilitated by hydrogen bonds, exhibits high dynamics and can lead to the detachment of the ammonium-halide ion pair during purification and upon exposure to air and light, , resulting in the formation of surface defects and increase of nonradiative recombination …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lead halide perovskite nanocrystals (PNCs) possess remarkable optical properties, such as high photoluminescence quantum yield (PLQY), large absorption coefficient, wide range bandgap tunability, and narrow emission line width. These characteristics make PNCs a promising material for optoelectronic applications, such as light-emitting diodes (LEDs), solar cells, , and photodetectors. , However, the ionic nature renders PNCs susceptible to light, heat, water, and polar solvents. Recent studies have shown that the rapid degradation of PNCs is primarily caused by the instability of their surface capping. The bonding between surface halides and ammonium ligands, facilitated by hydrogen bonds, exhibits high dynamics and can lead to the detachment of the ammonium-halide ion pair during purification and upon exposure to air and light, , resulting in the formation of surface defects and increase of nonradiative recombination …”
Section: Introductionmentioning
confidence: 99%
“…1−6 These characteristics make PNCs a promising material for optoelectronic applications, such as light-emitting diodes (LEDs), 7−9 solar cells, 10,11 and photodetectors. 12,13 However, the ionic nature renders PNCs susceptible to light, heat, water, and polar solvents. 14−16 Recent studies have shown that the rapid degradation of PNCs is primarily caused by the instability of their surface capping.…”
Section: Introductionmentioning
confidence: 99%
“…Organic-inorganic hybrid perovskites have attracted widespread attention in applications of solar cells, light-emitting diodes, and photodetectors, due to their excellent optoelectronic properties. [1][2][3][4][5][6][7][8][9] Especially in the field of photodetection, selfpowered perovskite photodetectors (PDs) play an important role in healthcare, bioimaging and other fields. 10,11 Among them, lead halide perovskite materials show high photocurrent and good stability, and have been widely studied in the field of photodetection.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Because of the simplicity of the system and tunable spectral responses, CCN-type NPDs hold the potential for developing novel optoelectronic devices. [9][10][11][12][13] However, the performances of CCN-type NPDs, such as EQE and SRR, depend on the active layer thickness and external bias, [14,15] and improving the figures-of-merit of such NPDs remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%